The Relationship Between the Amount of Time for Brace Wear and Its Psychological Effects and the Level of Social Participation of Adolescents With Spinal Deformity - Behdarvandan, Amin; Maktabi, Aida; Ghasemzadeh, Roya; Dastoorpor, Maryam (Majallah-i ilmī pizishkī-i jundīshāpūr, 2021)
Background and Objectives: Braces are common non-surgical treatments for the management of spinal deformities in adolescents. There are factors that may determine the success of non-surgical treatments of spinal deformities. Hence the aim of current study was to investigate the relationship between the amount of time for brace wear and its psychological effects and the level of social participation of adolescents with spinal deformity. Subjects and Methods we examined adolescents undergoing brace treatment for spinal deformity attending to Ahvaz Technical Orthopedic Centers. Among them, 30 adolescents including 3 males and 27 females (mean age: 14.7 (1.92) years) were included in the study. Sampling method was simple non-probability sampling. Data were collected using Fear of Negative Evaluation questionnaire, Participation Scale questionnaire, Bad Sobernheimer stress (Deformity) and Bad Sobernheimer (brace) questionnaire. The duration (hours and months) of brace treatment was also recorded. Statistical analysis was performed using Spearman correlation coefficient calculation and correlational analysis. Results The results demonstrated that the participation scale had a negative correlation with Bad Sobernheimer (brace) score (r= 0.49, p=0.006). Participation scale also had a positive correlation with fear of negative evaluation score (r= 0.42, p=0.019). There were no significant correlation between other variables. Conclusion Psycho-social factors can affect adolescents’ participation score undergoing brace treatment. People with scoliosis and hyper kyphosis undergoing brace treatment are young, so, it is important to consider psychological and social factors during brace treatment, to minimize negative consequences of brace treatment.